EEG power modulation in the sensorimotor regions is critical to motor tic suppression - Miyakoshi, Makoto; Jurgiel, Joseph; Dillon, Andrea; Piacentini, John; Makeig, Scott; Loo, Sandra K. (Frontiers in Psychiatry, 2025)
BackgroundThe neural mechanisms underlying tic suppression in chronic tic disorder (CTD) have been investigated using various neuroimaging modalities. A limitation in studying CTD is that abrupt motor action is inherent to the nature of the disorder, but the movement makes any form of neural recording challenging. However, recent advances in hardware and software technologies have enabled EEG studies during motion, which open new avenues for studying CTD with EEG.MethodsWe performed an event-related EEG power spectral analysis in children with chronic tic disorder (CTD) or typically developing children (TDC) as controls in a sample of 76 children (39 CTD) contributing to the final statistics. There were three block-separated conditions: no suppression (NoSupp), suppression with verbal instruction (SuppVrb), and suppression with reward (SuppRwd); the latter two conditions were collapsed into SuppAve. EEG data were processed using independent component analysis, and the event-related potential was decomposed in the time-frequency domain.ResultsDuring tic or blink suppression, both CTD and TDC showed EEG power increase centered within the theta range in frontal, cingulate, and central regions. Meanwhile, the CTD group showed the opposite pattern in broadband EEG power modulation relative to controls, particularly in the centro-temporal sensorimotor regions. The regression analysis between this broadband power and tic suppression performance resulted in a significant positive correlation.ConclusionsBetter tic suppression was associated with increased EEG power, a similar pattern observed among controls during blink suppression. EEG power in sensorimotor regions is a neural marker of tic suppression performance in children with CTD.